Thermophilic bacteria of the Verhne-Vilyuchinskie and Sredne-Paratunskie hot springs (Kamchatka, Far East) - Lebedeva Elena (E3S Web of Conferences)
The number of physiological groups, biodiversity, enzymatic activity and some physiological and biochemical properties of microorganisms isolated from thermal waters and microbial mats of Kamchatka were studied. A low content of microorganisms with a predominance of denitrifying (Verhne-Vilyuchinsky) and nitrifying bacteria (Sredne-Paratunsky springs) was shown. Gram-positive spore- forming rods of the genus Bacillus predominated among the isolated bacteria. The isolated microorganisms had extracellular enzymatic activity and were capable of growing in wide ranges of temperatures, pH and NaCl concentration. Strains of thermophilic bacteria are of interest for biotechnology purposes.